The Human Commitment as a Driving Force for Sustainable Development (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2026)
This issue of TEACS brings together research that, drawing on diverse disciplines and contexts, highlights the transformative potential of human commitment, social responsibility, and collective action. While the articles address a variety of issues, they all share a common concern: understanding and strengthening the processes that foster sustainable development, social inclusion, and the building of more resilient communities. Thus, this edition offers a multifaceted perspective on contemporary challenges and the role played by individuals, institutions, and organizations in driving socially significant change.